Māori identity and economic wellbeing - Houkamau, Carla (Routledge, 2019)
This chapter considers the link between ethnicity and economic wellbeing for the Māori of New Zealand. In the context of 175 years of colonization, identity and culture remain an important determinant of Māori people’s economic wellbeing. Drawing from diverse strands of literature, the chapter considers the relationship between identity, culture and economic practices for Māori. Empirical research related to Māori identity and economic preferences will be discussed, including a discussion of the link between cultural dimensions (collectivism/individualism) and Māori economic practices. Specific outcomes will be related to different sub-groups of Māori; including a discussion of the impacts of discrimination on Māori who are sole identifiers (i.e. two Māori parents) as opposed to mixed Māori/European. The positive impacts of enculturation for Māori subjective wellbeing will be outlined. Policy implications are also reviewed, particularly suggestions on how to develop appropriately tailored programmes which meet the cultural needs of Māori people.
Keywords: identity

Good data practices for indigenous data sovereignty and governance - Lovett, Raymond; Lee, Vanessa; Kukutai, Tahu; Cormack, Donna; Rainie, Stephanie; Walker, Jennifer (Institute of Network Cultures, 2019)
Indigenous Data Sovereignty (IDS) and Indigenous Data Governance (IDG) art terms increasingly being used across community, research, policy and in practice. The IDS movement has emerged in response to poor data practices, from the conceptualisation of data items through to reporting of data about Indigenous peoples. This chapter aims to provide clarity concerning the definitions of IDS and IDG; provide an overview of the historical context in which IDS has emerged; and provide examples of IDS and IDG across the spectrum of community, policy and practice.
Keywords: data; data sovereignty; statistics